De novo facioscapulohumeral muscular dystrophy defined by DNA probe p13E-11 (D4F104S1). Issue 3 (September 1994) - Jardine, P E; Koch, M C; Lunt, P W; Maynard, J; Bathke, K D; Harper, P S; Upadhyaya, M
Abstract : Facioscapulohumeral muscular dystrophy (FSHD) is an autosomal dominant condition with variable age of onset and severity. Identification of a de novo DNA fragment by probe p13E-11 (D4F104S1) established the diagnosis of new mutation FSHD in 27 of 31 sporadic cases. The clinical data for these certain new mutation cases were as follows: 13 boys, 14 girls; mean age of onset 6.8 years; significant leg weakness in 19/27 (70%) (8/27 (30%) used wheelchairs at a mean age of 17.7 years); high tone sensorineural deafness in 10/27; visual acuity and direct ophthalmoscopy were normal. Congenital facial diplegia and sensorineural deafness in three children suggest that infantile FSHD is not a genetically separate disorder from FSHD. Ascertainment bias may explain the difference in severity between this group and typical familial cases. Molecular analysis for FSHD should be considered in children with either congenital or early onset facial weakness or diplegia.